PRODUCTIVE ZAKAT DISTRIBUTION OF BUILDING VILLAGE MODEL TO INCREASE MUSTAHIQ INCOME - S Sahman Z; R Rizka; Muchammad Taufiq Affandi; Anindya Salsabila; M Muthoifin (Universitas Muhammadiyah Surakarta, 2023)
This study outlines the productive zakat distribution model, with the assisted village model developed by the National Amil Zakat Agency of Karanganyar Regency, which is expected to be able to convert mustahiq into munfiq or even muzaki more effectively and efficiently. BAZNAS or other zakat institutions have never done this model, so it is essential to examine its effectiveness, if it has a positive impact then this model needs to be developed by other institutions/agencies engaged in similar fields. This research is included in the type of field research with qualitative descriptive methods. The primary data in this study was obtained from the Head of Distribution and Utilization of BAZNAS Karanganyar, his Volunteer team, and Mustahik. Secondary data in this study was sourced from the 2020-2021 Karanganyar Regency BAZNAS Accountability Report and other relevant documents. Data collection techniques in this study are interview, observation and documentation techniques. The results showed that the distribution of productive zakat with the assisted village model was very effective, as evidenced by increasing income, developing mustahik businesses and being able to create jobs while increasing production and sales.